2018
DOI: 10.1111/bor.12326
|View full text |Cite
|
Sign up to set email alerts
|

Svalbard glaciers re‐advanced during the Pleistocene–Holocene transition

Abstract: Despite warming regional conditions and our general understanding of the deglaciation, a variety of data suggest glaciers re-advanced on Svalbard during the Lateglacial-early Holocene (LGEH). We present the first well-dated end moraine formed during the LGEH in De Geerbukta, NE Spitsbergen. This landform was deposited by an outlet glacier re-advancing into a fjord extending 4.4 km beyond the late Holocene (LH) maximum. Comparing the timing of the De Geerbukta glacier re-advance to a synthesis of existing data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…) that appear to be asynchronous and most likely result from dynamic instability during the deglaciation (Farnsworth et al . ).…”
Section: Revised Late Weichselian Glaciation History Of the Lower Bormentioning
confidence: 97%
See 1 more Smart Citation
“…) that appear to be asynchronous and most likely result from dynamic instability during the deglaciation (Farnsworth et al . ).…”
Section: Revised Late Weichselian Glaciation History Of the Lower Bormentioning
confidence: 97%
“…That would be in agreement with glacier records in Svalbard, which show widespread re‐advances during the Early Holocene (Lønne ; Farnsworth et al . ; Larsen et al . ) that appear to be asynchronous and most likely result from dynamic instability during the deglaciation (Farnsworth et al .…”
Section: Revised Late Weichselian Glaciation History Of the Lower Bormentioning
confidence: 99%
“…in de Geerbukta on northeast Spitsbergen, 60 km west of Palanderbukta, yielded a median age of 10.5 cal. kyr BP 25 . The RSL curves from Lady Franklinfjorden and Svartknausflya are the only other long RSL reconstructions from Nordaustlandet 5,6 .…”
Section: Discussionmentioning
confidence: 99%
“…This study from Wahlenbergfjorden highlights the complex spatial variability in glacier response during the deglaciation and early Holocene warming. Farnsworth et al 25 showed that a nearby major outlet glacier, Gullfaksebreen, in De Geerbukta at the west side of the Hinlopen Strait advanced in the early Holocene, a period characterized by mild climate and peak insolation (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation